Clinical epidemiological profile of snakebites in the city of Anápolis-Goiás from 2012 to 2019 - Braga Barbosa Ribeiro, Tatiana (2022)
Objective: to describe the clinical and epidemiological profile of snakebites in Anápolis-GO, in the period 2012-2019 Methods: This is a descriptive study, with data from the notification form of venomous animals (snakes) registered in the Department of Epidemiological Surveillance. Results: 572 cases were reported in the period; the highest frequency of cases was in males (78.8%); between the age group of 21-40 years (34.1%); occurring between December and April (53.7%); caused by the Bothrops genus (65.2%); accidents took around 1 to 3 hours to be seen (42.1%); stings prevailed in distal limbs (88.4%); cure was the most prevalent (97.7%) and 0.4% died from the accident. Conclusion: an important impact of seasonality was observed in this study and it is expected that the unpublished data from the sample obtained can serve as a substrate for the planning and execution of measures aimed at health surveillance and care.